(untitled) (International Journal of Innovative Research in Engineering & Management, 2024)
Time and adequate management of the scheduling of activities are very critical in every construction project. This study formulated a multiple linear regression optimization model to address issues bordering on delays in pile construction operations. A 300mm diameter reinforced concrete pile, 5.4m long, with a plastic casing was used. A total of 32 piles were constructed in a silty soil completely submerged in water at Bonny, Nigeria. The friction piles were constructed serially with a boring method, while the soil was extracted with the piling auger. The volumes of the extracted soil and concrete poured to fill the holes were accounted for, theoretically and actually. The same was done for the reinforcement cages installed in each pile shaft. The model was formulated and tested using Statistical Package for the Social Sciences (SPSS) software. The model was found to be fit, adequate, and highly accurate with an R2 value of 0.874.